Substance use disorder risk assessment: positive emotional experiences with first time use and substance use disorder risk - Arscott, Karen E.; Eget, Donna M.; Marcos, Maria C.; Piper, Brian J. (Frontiers in Psychiatry, 2024)
Introduction: Substance Use Disorder (SUD) screening tools used in current practice are designed to identify SUD once patients have begun dangerous drug use. While these screening tools are valuable, prevention and avoidance of SUD would save countless lives. This study addresses this care gap. The aim was to develop a simple screening tool for patients who may be prone to develop Alcohol Use Disorder (AUD) and/or SUD prior to addiction. It was hypothesized that participants with initially positive emotional experiences would be correlated with a future SUD diagnosis. Methods: The study involved a self-administered survey using a cross-sectional design and was carried out over one-month in the spring of 2021. Those patients who presented to the MAT clinic (SUD group) were seen in a separate area than the patients presenting for urgent care (Comparison group). Participants (N = 259) were voluntarily recruited from MAT and Urgent care: Patients receiving acute care were assigned to the Comparison (N = 126, 50.8% female, 5.7% non-white, 27.2 age < 34) and those receiving treatment for SUD were assigned to the MAT group (N =133, 40.8% female, 4.8% non-white, 36.8% <34). The survey questioned demographics (4 items), risk factors for AUD/SUD (6 items), information about first alcohol/opioid experiences (16 items), and factors for seeking AUD/SUD treatment and recovery (2 items). Feelings were categorized as positive (e.g., euphoria, happiness, self-confident), neutral (e.g., nothing, normal), or negative (e.g., depressed, sad, sick). Results: The MAT group felt more positive feelings with first usage of alcohol and opioids compared to the comparison group (p<.001). With first usage of opioids specifically, MAT (0.13 + 0.04) and comparison (0.29 + 0.07) groups differed (p <.001). Over half (55.3%), of the MAT participants reported feeling self-confident with first use of alcohol while only 29.7% of the comparison reported this (p<.001). Over three-fifths (63.7%) of the MAT group reported feeling of euphoria with the first usage of opioids compared to one-tenth (9.8%) in the comparison group (p<.001). Discussion: This retrospective cross-sectional report shows the first affective responses to substances may predict risk for future SUD and could be a prevention screening tool.